Current role of standardized uptake valuemax-derived ratios in N2 fluorine-18 fluorodeoxyglucose positron-emission tomography non-small cell lung cancer - Divisi, Duilio; Barone, Mirko; Crisci, Roberto (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Mediastinal staging is a crucial moment in management of non-small cell lung cancer (NSCLC) patients. In integrated pathways, 18-fluorine fluorideoxyglucose positron-emission tomography (18F-FDG-PET/CT) is an indispensable imaging resource with its peculiarities and its limitations. A critical review of work up protocols would certainly help to standardize procedures with important reflections also on the diagnostic value of this examination. In this regard, new semi-quantitative and semi-qualitative indexes have been proposed with the aim of increasing the accuracy of 18F-FDG-PET/CT in mediastinal lymph node staging. These latter, such as SUVn/t and SUV indexes, seem to overcome the problem of spatial resolution and discrimination of malignancy by endorsing a new predictive and prognostic role.